Asymmetry and international relationships - Womack, Brantly, 1947- (Cambridge : Cambridge University Press, 2016)
Power is real, but it does not always prevail. This book explores how disparity structures international relationships. Beginning at the bilateral level, the relationship between the smaller side and the larger side can be normal as long as the smaller does not feel threatened and the larger can assume that its capabilities are respected. However, the smaller can be tempted to brinksmanship, while the larger can be tempted to bully. Asymmetric conflicts are often stalemated because the limited commitment of the larger side is met by the smaller's mortal resistance. In multilateral situations, asymmetry shapes patterns of uncertainty and attention. In global systems, how hegemons treat their subjects is the unobserved sand shifting beneath their feet as they look toward their challenger. Since 2008, the US has retained primacy but not dominance. The management of asymmetric relationships in a multinodal world will determine how power matters in the current era.
Machine generated contents note: Introduction; Part I. Asymmetry and Bilateral Relationships: 1. Basic structure of asymmetric relationships; 2. Asymmetry and conflict; Part II. Asymmetric Systems: 3. Multilateral asymmetry; 4. Regional asymmetric relationships; Part III. World Systems: 5. Cycles and sustainability; 6. Multinodality and the status ad quem; Part IV. Policy Implications: 7. Asymmetric prescriptions.
Title from publisher's bibliographic system (viewed on 10 Dec 2015).
Keywords: International relations; Diplomacy